Determinants of MSME awareness to register BPOM Certification: An empirical study in the BBPOM Mataram Region - Irwan, Yosef Dwi; Widiyanesti, Sri (Keynesia : International Journal of Economy and Business, 2025)
Legal compliance in processed food products is a fundamental aspect of consumer protection and competitiveness for MSMEs in Indonesia. BPOM certification serves not only as a legal requirement but also as a strategic tool to access modern markets, financial support, and consumer trust. However, awareness among MSME actors to register for BPOM distribution permits remains low. This study aims to analyze the influence of knowledge, perceived benefits, perceived procedures, and BPOM support on awareness to register BPOM certification, with compliance as a mediating variable. Specifically, it investigates the indirect effects of knowledge, perceived benefits, and perceived procedures through compliance. The study employed a quantitative survey design involving 71 MSMEs in the jurisdiction of BBPOM Mataram that already possess a BPOM distribution permit (NIE). Data were collected via a Likert-scale questionnaire and analyzed using PLS-SEM with SmartPLS 3, including Importance-Performance Map Analysis (IPMA). Findings show that compliance and BPOM support significantly influence awareness, while knowledge, perceived benefits, and perceived procedures indirectly affect awareness through compliance. IPMA results position BPOM support and compliance in Quadrant I (high influence and performance), making them strategic priorities. The study contributes theoretically to the TPB framework by incorporating compliance as a behavioral mediator and offers practical recommendations for enhancing regulatory literacy, technical assistance, and procedural simplification.